Please solve this in inverse operations to understand it easily.
Hi Alex
-a - 13 = -10 --> We add 13 to each side (this cancels the -13 on the left side and adds 13 to -10 on the right)
-a = 3 ---> Now we divide each side by -1 to get a positive a (this gives us a positive a on the left side and a -3 on the right side).
Therefore, a = -3.
We substitute to check our answer...
-(-3) - 13 = -10 ---> so the two negatives make a positive 3 giving us 3 - 13 = -10, which is correct.
Thus, our answer a = -3 is correct.